2016
DOI: 10.14260/jemds/2016/1251
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Approaches to Intellectual Disability

Abstract: Substantial number of parents owing to ignorance, illiteracy and lack of proper and effective treatments used to take their children for various interventions such as magico-religious treatments, alternative medicines and unproved treatment modalities. AIMThe aim was to study the resource utilisation of the families of intellectual disability by taking a longitudinal history of various attempts to care children by the caregivers. MATERIALS AND METHODSIn an explorative study of resource utilisation of the famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[2] When the causes are unknown, prognosis is uncertain and the planning and provision of the services is difficult and the families tend to develop wrong beliefs, unrealistic expectations and may turn to other unproved alternative approaches of treatment. [2,8] Co-morbidity The study of McLaren and Bryson (1987) indicated that neurological disorders are frequently associated with MR, especially if the retardation is severe. [12] Seizure disorders in 15% -30% of patients, cerebral palsy and other motor handicaps were found in 20% -30% of patients and sensory impairments in 10% -20% of patients.…”
Section: Aetiologymentioning
confidence: 99%
See 1 more Smart Citation
“…[2] When the causes are unknown, prognosis is uncertain and the planning and provision of the services is difficult and the families tend to develop wrong beliefs, unrealistic expectations and may turn to other unproved alternative approaches of treatment. [2,8] Co-morbidity The study of McLaren and Bryson (1987) indicated that neurological disorders are frequently associated with MR, especially if the retardation is severe. [12] Seizure disorders in 15% -30% of patients, cerebral palsy and other motor handicaps were found in 20% -30% of patients and sensory impairments in 10% -20% of patients.…”
Section: Aetiologymentioning
confidence: 99%
“…[57] The difficulties faced by the relatives in the choice of the management plan and the vacillations in their approach are best revealed in a study done by the authors. [8] The observations of the study are as follows: 1. Considerable number of the parents have consulted other systems of management; 2.…”
Section: Yoga and Meditationmentioning
confidence: 99%